Iron decorated defective phosphorene as a viable hydrogen storage medium – A DFT study. (30th September 2022) - Srinivasan K V, Sai; Seth, Aqshat; Mohapatra, Dhammapada; Ramachandran, Shreyas; Sujith, Ravindran
Abstract: 2D materials like phosphorene have shown significant potential for hydrogen storage applications because of its large specific surface area and tuneable energetics. In this study, the effect of iron decoration on three defective phosphorene systems - DV-5|8|5-1, SV-5|9 and SV-55|66 - for hydrogen storage were studied theoretically using Density Functional Theory. Hydrogen adsorption energy in Fe-decorated DV-5|8|5-1 was calculated to be −0.562 eV/H2, which is within the DOE stipulated limit. Further analysis of P(3p) and Fe(3d) orbitals in Fe decorated DV-5|8|5-1 showed that both P and Fe contribute to the electronic interaction with H2, which was not seen in the other two single vacancy systems. Moreover, we observed that the magnetic moment of the systems plays an important role in hydrogen adsorption. H2 adsorbed Fe decorated DV-5|8|5-1 system with a magnetic moment of 2.04 μ B exhibited the highest H2 adsorption energy. These results indicate that such systems offer potential applications in magnetic heterostructures, catalysis and gas sensing applications. Highlights: Iron decoration on one DV and two SV defective phosphorene systems. Significant increase in H2 adsorption energy in Fe-DV-5.|8|5-1 system to −0.562 eV/H2 . Enhanced H2 adsorption due to high magnetic moment of 2.04 μ B /cell in H2 -Fe- DV system. Two step charge transfer mechanism at play: from Fe to P and P to H2 in DV system.